TRIBAL RELIGIONS - Manickam, Thomas (Journal of Dharma, 1992)
It is almost fashionable for Biblical scholars to trace the source of faith of all believers to the faith of Abraham, the ancient semitic tribal patriarch. In this search for the root of the faith of the believers in Judaism, Christianity and Islam we unwittingly acknowledge our common semitic tribal ancestory. In fact a considerable portion of our faith expressions are in the pattern of the prototype faith-experience and expression of Abraham: Abraham believed in Yahweh, and hoped against hope and trusted in God's saving power, and so it was credited to him for his righteousness before God. This short formula of faith and righteousness centred around the tribal patriarch Abraham has become classical in Biblical religions.